2022
DOI: 10.1186/s12876-022-02270-5
|View full text |Cite|
|
Sign up to set email alerts
|

Homogeneous and heterogeneous risk and prognostic factors for lung metastasis in colorectal cancer patients

Abstract: Background The lung is one of the most frequent distant metastasis sites in colorectal cancer (CRC) patients; however, lung metastasis risk and prognostic factors have not been comprehensively elucidated. This study aimed to identify the homogeneous and heterogeneous lung metastasis risk and prognostic factors in CRC patients using the Surveillance, Epidemiology, and End Results (SEER) database. Methods CRC patients registered in the SEER database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Several studies have consistently demonstrated that factors such as advanced age, elevated histological grade, and larger tumor size exhibit a negative correlation with long-term survival outcomes [ 8 , 18 , 19 ]. In our investigation, the findings underscore a significant disparity in survival rates between patients who underwent surgical treatment and those who did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have consistently demonstrated that factors such as advanced age, elevated histological grade, and larger tumor size exhibit a negative correlation with long-term survival outcomes [ 8 , 18 , 19 ]. In our investigation, the findings underscore a significant disparity in survival rates between patients who underwent surgical treatment and those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed a lower survival rate among patients aged 70 years and older. This age-related discrepancy in survival rates may be associated with compromised immunity and physical deterioration commonly observed in elderly patients [ 18 , 19 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…After publication of this article [ 1 ], the authors reported that in this article there is a superfluous line in Fig.¬† 1 ; the figure should have appeared as shown below.
Fig.
…”
Section: Correction To: Bmc Gastroenterology (2022) 22:193 101186/s1...mentioning
confidence: 99%